The relationship between mentorship and internship students growth mindset: The mediating role of intrinsic motivation and work engagement - Suksesi, Muhammad Adhi Makayasa Garuda; Nurihsan, Juntika; Gustiana, Asep Deni (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This study aimed to examine the relationship between mentorship and growth mindset among interns, with intrinsic motivation and work engagement as mediating variables. Using a quantitative approach with a correlational explanatory design, data were collected from university students participating in internship programs through a Likert-scale questionnaire adapted from standardized instruments measuring mentorship, intrinsic motivation, work engagement, and growth mindset. Data were analyzed using the Structural Equation Modeling (SEM) technique. The results indicated that mentorship had a positive and significant effect on the growth mindset of interns. Furthermore, intrinsic motivation and work engagement were found to partially mediate this relationship, implying that effective mentor support should be complemented by internal motivation and active involvement from students to optimize the development of a growth mindset. These findings highlight the importance of collaborative efforts between educational institutions and internship programs in developing comprehensive mentoring systems. Theoretically, this study contributes to the literature on educational and organizational psychology, while practically offering insights for designing internship programs that foster adaptive, resilient, and motivated future professionals.